In vıtro determınatıon of the skın antı-agıng potentıal of centaurea urvılleı dc. Subsp. Armata wagenıtz (Bangladesh Journal of Botany, 2025)
This study investigated the potential of the ethanolic extract of Centaurea urvillei DC. subsp. armata WAGENITZ for use in dermatological treatments. This evaluation involved the assessment of its sun protection factor (SPF), inhibitory effects on extracellular matrix-degrading enzymes, antioxidant activity, as well as genotoxic and antigenotoxic properties. The results demonstrated that the extract exhibited a significant SPF value (11.755) and inhibited collagenase, elastase, and hyaluronidase enzymes. Additionally, the extract revealed significant antioxidant activity, as evidenced by its prominent DPPH (IC50 = 2.35 mg/ml) and β-carotene/linoleic acid (IC50 = 0.802 mg/ml) inhibitory effects. Furthermore, genotoxicity tests revealed no harmful effects, while antigenotoxicity assessments indicated its potential to protect against DNA damage. These findings underscore the potential of C. urvillei subsp. armata as a promising bioactive plant for natural skin anti-aging cosmetic formulations.Bangladesh J. Bot. 54(2): 239-244, 2025 (June)